Energetic Oxygen and Sulfur Charge States in the Outer Jovian Magnetosphere: Insights From the Cassini Jupiter Flyby - Allen, R. C. (Geophys Res Lett, 2019)
On 10 January 2001, Cassini briefly entered into the magnetosphere of Jupiter, en route to Saturn. During this excursion into the Jovian magnetosphere, the Cassini Magnetosphere Imaging Instrument/Charge‐Energy‐Mass Spectrometer detected oxygen and sulfur ions. While Charge‐Energy‐Mass Spectrometer can distinguish between oxygen and sulfur charge states directly, only 95.9 ± 2.9 keV/e ions were sampled during this interval, allowing for a long time integration of the tenuous outer magnetospheric (~200 R(J)) plasma at one energy. For this brief interval for the 95.9 keV/e ions, 96% of oxygen ions were O(+), with the other 4% as O(2+), while 25% of the energetic sulfur ions were S(+), 42% S(2+), and 33% S(3+). The S(2+)/O(+) flux ratio was observed to be 0.35 (±0.06 Poisson error).